Genetic variants of 20q12 contributed to non‐syndromic orofacial clefts susceptibility. (13th September 2016) - Yin, X; Ma, L; Li, Y; Xu, M; Wang, W; Wang, H; Yuan, H; Du, Y; Li, S; Ma, J; Jiang, H; Wang, L; et al.
Abstract : Objective: Previous genomewide association studies (GWAS) identified a region near MAFB at chr20q12 associated with non‐syndromic orofacial clefts (NSOC) susceptibility. However, whether other SNPs in this area could independently contribute to non‐syndromic orofacial clefts in Chinese populations remained obscure. Materials and Methods: We selected 24 SNPs based on a haplotype‐tagging SNP strategy and evaluated their associations with risk of non‐syndromic orofacial clefts in a large‐scale two‐stage case–control study with 1278 cases and 1295 controls. Genotyping was performed with Sequenom and TaqMan assay. Associations between the SNPs and risk of non‐syndromic orofacial clefts were estimated from unconditional logistic regression analyses. Results: Overall, six SNPs were found to be the susceptible factors of non‐syndromic orofacial clefts. The most significant and independent SNP was rs6129653 (additive model of P value = 1.4E‐06). In subgroup analysis, its significant associations with cleft lip only (CLO) and cleft lip and palate (CLP) were observed. Furthermore, in silico bioinformatics analysis indicated that rs6129653 was located in the transcriptionally active region and associated with MAFB expression in human brain tissues. Conclusions: Rs6129653 was an independent locus of non‐syndromic orofacial clefts among Chinese populations possibly due to its potential of distal transcriptional regulation of MAFB expression.